Binding of glycosaminoglycans to the surface of Treponema pallidum and subsequent effects on complement interactions between antigen and antibody. Issue 1 (February 1985) - Fitzgerald, T J; Miller, J N; Repesh, L A; Rice, M; Urquhart, A
Abstract : Acidified bovine serum albumin (acid BSA) reacts with glycosaminoglycans to form a precipitate. This reaction was adapted to Treponema pallidum to show glycosaminoglycans associated with the surface of the micro-organism. As testicular infection progressed from days 4 to 18, treponemes showed increasing amounts of these surface components. High speed centrifuging effectively removed the glycosaminoglycans, thus indicating that they were loosely bound. The subsequent addition of commercial preparations of hyaluronic acid or chondroitin sulphate resulted in their immediate adherence to the surface of the pathogens T pallidum and T pertenue, but not to the non-pathogens T vincenti, T denticola, or T phagedenis. The amount adhering to the treponemal surface varied depending on the concentration added. Intradermal inoculation showed that the virulence of T pallidum was not altered by the glycosaminoglycans associated with its surface. The coating of treponemes with hyaluronic acid or chondroitin sulphate did not interfere with neutralising antibodies or antibodies found by radioimmunoassay using whole organisms. In contrast, hyaluronic acid or chondroitin sulphate on the treponemal surface did interfere with immobilising antibodies. Results are discussed in terms of the potential role of the treponemal glycosaminoglycans in the infectious process.